A beautiful little fool? Retranslating Daisy Buchanan in The Great Gatsby. (3rd September 2021) - Zeven, Katinka; Dorst, Aletta G.
ABSTRACT: This paper explores how ideas about gender are captured in literary works, and how such ideas are reinforced, revised or rejected in (re)translation. It does so by examining the two Dutch translations of The Great Gatsby, focusing on the characterization of Daisy Buchanan. The analysis draws attention to the influence that translators may – either consciously or unwittingly – have on gender stereotyping. By cataloguing the differences in the portrayal of Daisy Buchanan between the first translation and the retranslation, this paper sheds light on the ideological implications of translation choices and the way they affect how readers perceive characters and their gender roles. The analysis shows that both translations, but the older translation in particular, paint a more negative picture of Daisy than the original does: both make Daisy more manipulative and emphasize her perceived seductiveness. The comparison shows that translation decisions may have serious impact on the way in which female characters are portrayed, and how preconceived ideas about gender may be reinforced as a result of a (mis)reading of the original.